How do Streptomyces coordinate DNA repair and cell division following DNA damage?. Issue 5 (27th May 2022) - Stratton, Kathryn; Bush, Matthew; Chandra, Govind; Findlay, Kim; Schlimpert, Susan
Abstract : DNA damage often results in a pause of cell division until damage is repaired. In bacteria, a widely conserved response to DNA damage is the SOS response which relies on two proteins: the multifunctional recombinase RecA and the transcriptional repressor LexA. Under DNA-damaging conditions, this response activates proteins involved in DNA repair and the inhibition of cell division which in most unicellular bacteria results in temporarily filamentous growth. However, it is unknown how naturally filamentous growing bacteria like Streptomyces cope with DNA damage and how DNA damage repair is coordinated with cell division. To identify novel regulators of cell division in Streptomyces that specifically function during DNA damaging growth conditions, we investigated the global response of Streptomyces venezuelae to several genotoxic agents, including mitomycin C, ciprofloxacin and methane methylsulfonate. To this end we have performed ChIP-seq experiments to identify the LexA regulon in Streptomycesandconducted RNA-seq experiments to determine the global response to DNA damaging agents in the wildtype and a recA mutant. The combined analysis of the available data sets has allowed us to obtain a comprehensive overview about the genes involved in the SOS response in Streptomycesand further analysis will enable us to understand how damage repair and cell division are coordinated in these bacteria.